CONCEPTION OF THE SCHOOL WORKROOM AND TECHNICAL FACILITIES AT CONTEMPORARY PARADIGM OF TECHNOLOGY - TVARUZKA, Vaclav (Trends in education, 2020)
The paper deals with the ideal facilities for technological education from the contemporary possibilities and perspectives extasciiacute point of view. The author proceeds from his pedagogical practice in condition of primary school. There was a special wing of the school building fully used due to its spatial and technical facilities. The paper deals with a workroom equipment from the contemporary trends of education extasciiacutes point of view in developed countries.
Keywords: practical activities; technical and vocational education; technology; small material